Entre cronos e kairós: a auto-percepção da idade na velhice - Bertamoni, Hélia Fraga Gomes (2009)
Temporality is lived by men through both chronological and existential terms. Such paired experience of temporality frequently unfolds on what we can name as the hiatus between the real and the conceived age. In most cases, the selfperception of age leads to subtraction of years of life, being rare the cases which self-attributed age matches and even increases the real age. That is the topic of this dissertation which has gone not only into authors whose works are molded by diverse philosophies and scientific traditions but also into aesthetics through poets and composers. The main objective was to investigate the proximity and the distance between the chronological and conceived ages among individuals in Health Care. Alongside and according to the individuals, we have also come up with conceptions of aging and old age. From a methodological point of view the option was for the qualitative approach. For being an approach that allows exploration of conceptions and wishes, normally odd to the oriented quantitative approaches, our option provided attributed meanings given by the individuals so as chronos (chronological) and kairos (existential) temporalities could be unveiled